Democratic Innovations - between Deliberation and Civic Participation - Grygieńć, Janusz (Sensus Historiae, 2022)
The theory of deliberative democracy has undergone radical transformations in recent decades. One of the most important of these has undoubtedly been its ‘institutional turn,’ i.e. the shift from normative reflections on the deliberative ideal to the analysis of specific institutional solutions designed to implement it. The purpose of this article is to analyse the place that one such solution, democratic innovations (ID), occupies in contemporary political philosophy and theory. In this article, I define ID as an attempt to reconcile the ideals of participatory and deliberative democracy. As a compromise project, ID does not fully satisfy either the proponents of deliberative democracy or the apologists of participatory democracy. The article discusses three unavoidable negative consequences of IDs, which are also the basis for their criticism: their social unrepresentativeness, lack of political agency and non-deliberative character.